2022
DOI: 10.3389/fped.2022.863919
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Functional Tic-Like Behaviors: What Do the COVID-19 Pandemic and Social Media Have to Do With It? A Narrative Review

Abstract: BackgroundThere has been a rise in explosive onset of tic-like behaviors during the COVID-19 pandemic. Historically, this is an uncommon phenomenology of functional movement disorders across all ages. Both the psychological burden of the pandemic and social media usage have been implicated in the rise of these tic-like behaviors.MethodsThis paper provides a narrative review of the literature on chronic tic disorders, functional tics, and mass functional illness with particular focus on the key distinguishing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 147 publications
(243 reference statements)
0
28
0
1
Order By: Relevance
“…Overall, these differences suggest the existence of two possible subtypes of FTLB [16], one related and one unrelated to social modelling. Within the former, a minority of patients also reported in-person exposure to individuals, usually within their peers, experiencing tics or tic-like behaviours.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, these differences suggest the existence of two possible subtypes of FTLB [16], one related and one unrelated to social modelling. Within the former, a minority of patients also reported in-person exposure to individuals, usually within their peers, experiencing tics or tic-like behaviours.…”
Section: Discussionmentioning
confidence: 94%
“…While there are clear differences between the disorders, TS and FTLB also share some common features. Both TS and FTLB are subject to suggestibility and distractibility [ 4 ••, 7 ••, 23 , 24 ••]: both categories of behaviors can be triggered or aggravated by directing the focus of communication toward the behaviors and by intercurrent stressors, and both can be alleviated by re-orienting attention toward other attention-demanding tasks (particularly tics) or simply away from the behaviors (particularly FTLB).…”
Section: Phenomenology: Contrasting Functional Tic-like Behaviors And...mentioning
confidence: 99%
“…31 During the pandemic, there was an increased interest in TS via social media, leading to "#tourette" being viewed nearly 5 billion times on the TikTok platform alone. 3,49 Social media can, in fact, be a positive support system in which users have acknowledged that social media portrayals of tics have led to peer support and a sense of belonging. 24 However, there may be unintended consequences of viewing inaccurate portrayals of tics on social media, including reinforcement of maladaptive behaviors.…”
Section: Portrayal Of Tics In Social Mediamentioning
confidence: 99%
“…Although there was no significant worsening of symptoms in patients who have preexisting FMD, there was an increase in the number of people who newly presented to clinic with FMD during the pandemic. 19,49,51 At least one study reported a 60.1% increase in new patients diagnosed with FMD between March 1, 2020 and October 30, 2020. 19 The majority of these new presentations occurred in female patients (75.6%), and the most common type of functional movement disorder reported was tremor (53.3%) followed by dystonia (31.1%).…”
Section: Functional Movement Disorders (Fmds)mentioning
confidence: 99%
See 1 more Smart Citation